Developing a knowledge translation program for health practitioners: Allied Health Translating Research into Practice - Young, Adrienne M.; Cameron, Ashley; Meloncelli, Nina; Barrimore, Sally E.; Campbell, Katrina; Wilkinson, Shelley; McBride, Liza-Jane; Barnes, Rhiannon; Bennett, Sally; Harvey, Gillian; Hickman, Ingrid (Frontiers in Health Services, 2023)
Background: Front-line health practitioners lack confidence in knowledge translation, yet they are often required to undertake projects to bridge the knowledge-practice gap. There are few initiatives focused on building the capacity of the health practitioner workforce to undertake knowledge translation, with most programs focusing on developing the skills of researchers. This paper reports the development and evaluation of a knowledge translation capacity building program for allied health practitioners located over geographically dispersed locations in Queensland, Australia. Methods: Allied Health Translating Research into Practice (AH-TRIP) was developed over five years with consideration of theory, research evidence and local needs assessment. AH-TRIP includes five components: training and education; support and networks (including champions and mentoring); showcase and recognition; TRIP projects and implementation; evaluation. The RE-AIM framework (Reach, Effectiveness, Adoption, Implementation Maintenance) guided the evaluation plan, with this paper reporting on the reach (number, discipline, geographical location), adoption by health services, and participant satisfaction between 2019-2021. Results: A total of 986 allied health practitioners participated in at least one component of AH-TRIP, with a quarter of participants located in regional areas of Queensland. Online training materials received an average of 944 unique page views each month. A total of 148 allied health practitioners have received mentoring to undertake their project, including a range of allied health disciplines and clinical areas. Very high satisfaction was reported by those receiving mentoring and attending the annual showcase event. Nine of sixteen public hospital and health service districts have adopted AH-TRIP. Conclusion: AH-TRIP is a low-cost knowledge translation capacity building initiative which can be delivered at scale to support allied health practitioners across geographically dispersed locations. Higher adoption in metropolitan areas suggests that further investment and targeted strategies are needed to reach health practitioners working in regional areas. Future evaluation should focus on exploring the impact on individual participants and the health service.